Development at the Border : Policies and National Integration in Côte D'Ivoire and Its Neighbors - Cogneau, Denis; Mesplé-Somps, Sandrine; Spielvogel, Gilles (Oxford University Press on behalf of the World Bank, 2016)
By applying regression discontinuity designs to a set of household surveys from the 1980–90s, we examine whether Côte d'Ivoire's aggregate wealth was translated at the borders of neighboring countries. At the border of Ghana and at the end of the 1980s, large discontinuities are detected for consumption, child stunting, and access to electricity and safe water. Border discontinuities in consumption can be explained by differences in cash crop policies (cocoa and coffee). When these policies converged in the 1990s, the only differences that persisted were those in rural facilities. In the North, cash crop (cotton) income again made a difference for consumption and nutrition (the case of Mali). On the one hand, large differences in welfare can hold at the borders dividing African countries despite their assumed porosity. On the other hand, border discontinuities seem to reflect the impact of reversible public policies rather than intangible institutional traits.